Does financial speculation with agricultural commodities cause hunger? A reply to our critics - Matthias Georg Will; Sören Prehn; Ingo Pies; Thomas Glauben (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2013)
As a reply to our critics, we show that Bozorgmehr et al. (2013) have (a) misunderstood, (b) misread, and (c) misinterpreted the literature review by Will et al. (2012). – – Als Antwort auf unsere Kritiker zeigen wir, dass Bozorgmehr et al. (2013) den Literaturüberblick von Will et al. (2012) (a) falsch verstanden, (b) falsch gelesen und (c) falsch interpretiert haben.
Keywords: D84; G12; G13; G14; Q13; Q18; 330; Financial speculation; futures market; agricultural commodities; regulation; position limits; transaction tax; volatility; price level; Finanzspekulation; Terminmarkt; Agrarrohstoffe; Regulierung; Positions-Limits; Transaktionssteuer; Volatilität; Preisniveau; Rohstoffspekulation; Unterernährung